2020
DOI: 10.1042/bsr20193353
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin signaling as an emerging potential key pharmacological target in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a fatal malignant tumor of biliary epithelial cells involving intra- or extra-hepatic bile ducts. The prognosis of CCA is generally poor due to its diagnosis at the late stages. The currently employed chemotherapeutic agents do not increase the survival rate in patients with unresectable CCA. Accordingly, there is a need to identify new therapeutic agents for the effective management of intra- and extra-hepatic CCA. Clinical as well as preclinical studies have suggested the key role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 84 publications
0
20
0
Order By: Relevance
“…WNT11 is notably upregulated in a liver injury model, and it may be arising from macrophages ( Jiang et al, 2019 ). Clinical and preclinical studies have shown that activation of the Wnt signaling pathway plays a key role in the induction and progression of cholangiocarcinoma ( Zhang et al, 2020 ). In bile duct-ligated mice, adenovirus carrying Dickkopf-1 (WNT antagonist) was able to significantly reduce cholangiocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…WNT11 is notably upregulated in a liver injury model, and it may be arising from macrophages ( Jiang et al, 2019 ). Clinical and preclinical studies have shown that activation of the Wnt signaling pathway plays a key role in the induction and progression of cholangiocarcinoma ( Zhang et al, 2020 ). In bile duct-ligated mice, adenovirus carrying Dickkopf-1 (WNT antagonist) was able to significantly reduce cholangiocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are known to play important roles in the progression of multiple diseases, including hepatic carcinoma (25,26). We found that a miR-513a-5p antagomir partially reversed the inhibitory effect of LINC01234 knockdown on liver cancer.…”
Section: Discussionmentioning
confidence: 73%
“…This suggested that the ClC-5 knockdown decreased the Wnt/β-catenin signal transduction pathway. Growing evidence suggests that inhibition of the Wnt/β-catenin signaling pathway can inhibit CCA progression ( 26 - 28 ). Furthermore, β-catenin degradation can activate the mitochondrial apoptotic pathway by promoting Bax translocation ( 29 - 31 ).…”
Section: Discussionmentioning
confidence: 99%